Peningkatan Kesadaran Gizi Seimbang dan Pencegahan Stunting melalui Edukasi dan Demo Masak di Desa Dieng - Aura Aulia; Radite Ranggi Ananta (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
Malnutrition issues such as stunting remain a serious problem in Dieng Village, despite the area's great potential in the agricultural sector. The main factors causing stunting include a lack of community knowledge about nutrition, low compliance with posyandu activities, and suboptimal food processing. This community service activity aims to increase the knowledge of mothers with stunted toddlers and pregnant women with Chronic Energy Deficiency (CED) about balanced nutrition and stunting prevention efforts. The program targets 18 mothers with stunted toddlers and 2 pregnant women with CED. The activities included counseling sessions on the three types of food, balanced nutrition guidelines, and the importance of posyandu, using leaflets as media, followed by a cooking demonstration on how to make chicken and tofu nuggets as a high-protein menu that is easy to make. Based on the evaluation results, there was a significant increase in participants' knowledge, from an average pre-test score of 65% to 97.5% on the post-test. In addition, the enthusiasm and active participation of participants during the question and answer session showed that the combination of theoretical education and hands-on practice was effective in increasing awareness and understanding of nutrition and stunting prevention.